Sosialisasi Pola Hidup Bersih dan Sehat (PHBS) bagi Siswa Sekolah Dasar di Kota Palangka Raya Pada Masa New Normal - Yudo Harvianto; Cukei; Yossita Wisman; Garry William Dony (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
President of the Republic of Indonesia, Joko Widodo, during his official speech at the Merdeka Palace, stated that the Indonesian people must remain vigilant at this time, even though the spread of the Covid 19 outbreak has begun to decrease. To overcome this, all people should continue to apply new habits in the order of life. Many people call this new normal order the New Normal. One of the goals of implementing the New Normal is so that people can live productively as long as there is still a pandemic outbreak of covid 19. The most effective way to prevent the covid 19 outbreak at this time is by adopting a clean and healthy lifestyle such as doing sports in an organized manner and measurable, and consume nutritious food. A clean and healthy lifestyle in schools is the implementation of certain health procedures by empowering teachers, students and the community around the school. They are expected to carry out a clean and healthy lifestyle to create healthy schools and environments as well. Based on the background above, the author conducts socialization on the Importance of a Clean and Healthy Lifestyle for Elementary School Students in Palangka Raya City during the New Normal Period. The purpose of holding this socialization activity is that it is hoped that students can carry out a healthy lifestyle in their daily lives, so that it is hoped that they will not be susceptible to contracting the Covid-19 virus. The method used in this activity is face-to-face socialization. Socialization activities are carried out by explaining the importance of a clean and healthy lifestyle. After that, a discussion session was held. This activity was carried out in several elementary schools in Palangka Raya City. Based on the community service activities that have been carried out, it can be concluded that the outreach activities for Clean and Healthy Lifestyles for Elementary School Students in Palangka Raya City during the New Normal Period, can provide education regarding the prevention of transmission of the covid-19 virus for students through routine hand washing with soap, consume nutritious food, exercise regularly and measuredly, get enough rest, keep your distance and wear a mask. This can be seen in the activeness of students asking questions during discussion sessions, and being able to answer when asked questions.